MOLECULAR DIAGNOSIS OF MULTICENTRIC CANINE LYMPHOMA IN A BOXER – A CASE REPORT - Laya V Reddy; D Selvi; K. Rajkumar; A. Abiramy @ Prabavathy; P. Vijayalakshmi (The Indian Veterinary Journal, 2026)
A 12-year-old cachectic male Boxer weighing around 18.2 kg was presented to the Department of VMD, VCC, RIVER with a history of inappetence, weakness, recumbency, polyuria and polydipsia for the past month. Physical examination revealed multifocal moist erosive plaques on the limbs, icteric conjunctival and buccal mucosae, and generalised lymphadenopathy. Lymph node aspirate was collected in PBS and sent for PARR (PCR for Antigen Receptor Rearrangement assay), which revealed the clonality of B and T-cell receptors, confirming the case as lymphoma. Owing to the senility of the patient and correlated poor prognosis, the owner objected to commence chemotherapy. Therefore, the pet was treated symptomatically. This paper emphasises the applicability of the PARR assay, a sensitive tool to differentiate between types of lymphoma and the associated outcome of the case.